IMPLEMENTATION OF LEVELS OF INQUIRY ON SCIENCE LEARNING TO IMPROVE JUNIOR HIGH SCHOOL STUDENTâS SCIENTIFIC LITERACY - Arief, M. K.; Utari, S. (Physics Department, Faculty of Mathematics and Natural Sciences, Semarang State University, 2015)
Scientific literacy is the key learning Â outcomes for all students. Based on observation, scientific literacy of student is less facilitated in scienceÂ learning.Â Learning of levels of inquiry is one ofÂ solution alternative to increase science literacy. So that, that aim of this study to improve scientific literacy for junior high school students through implementing levels of inquiry in science learning with the theme of global warming. This study used a weak experimental with one group pretest-posttest design. The sample in this study are 35 student at 7thÂ grade at junior high school in Second semester in academic year 2014/2015. The data of this study is taken by scientific literacy test. The results showed that explain phenomena scientifically competence and interpret data and evidence scientifically competence has increased significantly. Meanwhile, evaluate and design scientific enquiry competence is not significantly increased. In addition, the domain knowledge indicates that the three aspects of the knowledge which consist of content knowledge, procedural knowledge, and epistemic knowledge has increased significantly.Â Literasi sains merupakan hasil belajar kunci bagi semua siswa. Berdasarkan hasil observasi, literasi sains siswa kurang difasilitasi dalam proses pembelajaran IPA di kelas. Pembelajaran levels of inquiry merupakan salah satu alternatif solusi untuk meningkatkan literasi sains. Oleh karena itu, tujuan penelitian ini adalah untuk meningkatkan literasi sains siswa SMP melalui penerapan levels of inquiry pada pembelajaran IPA tema pemanasan global. Penelitian ini menggunakan metode eksperimen lemah dengan desain penelitian one group pretest-posttest. Sampel dalam penelitian ini adalah 35 siswa kelas VII SMP pada semester genap tahun pelajaran 2014/2015. Data penelitian diperoleh melalui tes literasi sains. Temuan dalam penelitian ini adalah kompetensi menjelaskan fenomena ilmiah dan kompetensi menginterpretasikan data dan bukti ilmiah meningkat secara signifikan. Sedangkan, kompetensi mengevaluasi dan merancang penyelidikan ilmiah tidak meningkat secara signifikan. Selain itu, pada domain pengetahuan menunjukkan bahwa ketiga aspek pengetahuan yaitu pengetahuan konten, pengetahuan prosedural, dan pengetahuan epistemik meningkat secara signifikan.Â